Cases on online tutoring, mentoring, and educational services practices and applications - Berg, Gary A., 1955- (Information Science Reference, 2010)
"This book examines the rapidly developing sector of online tutoring and mentoring, featuring case studies of the adaptation of university-based programs for tutoring and mentoring"--Provided by publisher.